Dye-liquid-crystal-based biosensing for quantitative protein assay. (March 2018) - Wu, Po-Chang; Karn, Abhishek; Lee, Mon-Juan; Lee, Wei; Chen, Chao-Yuan
Abstract: Dye liquid crystals (DLCs) have been extensively investigated in the field of liquid crystal display, but their potential in biosensing has not been explored. To provide insights into the potential of DLCs as a means of biosensing material, a DLC-based biosensor was developed for protein detection and quantitation. Unlike dye-doped LCs, the DLC used in this study contains an azobenzene LC molecule chemically modified with two azo groups as chromophores, enabling the DLC to exhibit unique optical anisotropy and dichroic absorption at 470 nm, which were exploited in the quantitation of bovine serum albumin (BSA). The change in orientation of DLC molecules from the homeotropic to a disrupted state by BSA immobilized on the aligning-layer surface was evaluated in terms of the relative loss in transmittance, expressed by the standard parameter S %, due to the absorption as well as scattering of light. The DLC-based protein assay was capable of determining the BSA concentration, with which S % varied linearly between 1  μ g/ml and 7.5  μ g/ml. When the DLC molecules were reoriented from a BSA-disrupted state to the homeotropic alignment by an externally applied electric field, a linear correlation between S % and BSA concentration could be also derived from the voltage–transmittance plots. The unique electro-optical properties of the intrinsically dichroic DLC are promising toward the development of a simple and reliable sensing platform for the quantitative analysis of biomolecules. Highlights: A dye-liquid-crystal (DLC) was synthesized and a DLC-based biosensor is developed for quantitative protein detection. The DLC as the biosensing element exhibits unique features of optical anisotropy and dichroic absorption at 470 nm. Concentrations of the model protein BSA between 1  μ g/ml and 7.5  μ g/ml were discernible by transmission spectroscopy. A standard parameter with a linear correlation to BSA concentration is established by the transmittance variation at 470 nm.